Analysis of Characteristic Flavor Compounds of Yak Meat in Different Regions Based on GC-IMS - Yahui GUO; Yunna LIU; Haiyue WU; Rong HU; Zhongxin YAN; Xun WANG; Yang XIANG; Haijia REN; Bo HU (Shipin gongye ke-ji, 2025)
To understand the differences in the characteristic flavor substances of yak meat from different regions, the volatile flavor compounds in yak meat from three different regions, Qinghai Guoluo (QH), Sichuan Aba (SC) and Yunnan Shangri-La (YN) were qualitatively determined by gas chromatography-ion mobility spectrometry (GC-IMS). The characteristic flavor substances of yak meat in different regions were distinguished by fingerprint, principal component analysis and relative odor activity calculation of volatile compounds. There were significant differences in the composition of flavor compounds in yaks from different regions (P<0.05), and a total of 26 volatile flavor compounds were detected in yak meat from the three regions. By drawing the fingerprints, the highest concentration of the substances in region A was found in the yak meat from Guoluo, Qinghai, the highest concentration of the substances in region B was found in the yak meat from Aba, Sichuan, and the highest concentration of the substances in region C was found in the yak meat from Shangri-La, Yunnan. The PCA score situation indicated that yak meat from each region had unique aroma substances, and the concentration of volatile substances in yak meat from Yunnan Shangri-La was higher than that in the other two regions. The ROAV value of 2,3-butanedione, n-octanal, n-nonanal , and 2-pentanone monomer was greater than 1 according to the content of relative odor activity value of yak meat, indicated that these four substances were the key substances affecting the flavor differences of yak part meat. Therefore, GC-IMS can effectively distinguish the volatile compounds and provide a theoretical basis and data support for the study of the characteristic relationship between volatile flavor substances in yak meat from different regions.